Improving Students’ Ability in Writing Recount Text by Using Lexicon List at First Year Of SMA Negeri 3 Palangka Raya in Academic Year 2011/2012 - Susva Amiyana (UMBanjarmasin, 2020)
The objective of this study is to find out the connection between lexicon list and students’ ability in writing recount text and to find out the degree of the students’ improvement of writing recount text at the first year of SMA Negeri 3 Palangka Raya in academic year 2011/2012. The subject involved in this study was the first year students of SMA Negeri 3 Palangka Raya. The writer used X-3 which gets the lowest score for writing skill the class consists of 35 students. The research method that used in this study was classroom action research. This classroom action research was carried out by the researcher collaboratively with the teacher in the first year students of SMA Negeri 3 Palangka Raya by implementing lexicon list. The writer described improvement in students’ writing skill through several procedures such as identifying the problem, carrying out the real classroom research such as planning, implementing the action, observing and reflecting the observation result and the last doing evaluation. According to the result of post-test on every end of the cycle, the increase of the students’ achievement was recorded. At the pre-test was 38.17 % (Very Poor), Post-test cycle I was 55.23 % (Poor), and at Post-test cycle II was 73.03 % (Good). This indicated that there was an increase by 17.06 % from pre-test to post-test cycle I and 17.8 % from post-test cycle I to post-test cycle II. Total increase from pre-test to post-test cycle II was 34.86 %. This means that lexicon list method positively increase students’ writing skill on recount. In addition to test results, the results of questionnaires showed that students had difficulty in understanding the recount text. The students agree that in the teaching learning process using the media as motivation and attraction students in learning English especially recount text.